2005
DOI: 10.1097/01.mao.0000169785.15083.28
|View full text |Cite
|
Sign up to set email alerts
|

Changes In Blood Neurotransmitter And Steroid Levels During Evoked Vertigo

Abstract: Evoked vertigo is consistently associated with an increase in steroid serum levels and accompanying decreases in the plasma levels of glutamate, aspartate, and GABA. The possible underlying mechanisms and the functional significance of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In the present study, we demonstrated that the air CVT, a useful medical examination procedure that assesses the horizontal semicircular canal function of each labyrinth and is severe enough to provoke nystagmus and dizziness, is a powerful activator of the HPA axis, a finding that aligns with previous observations made by Dagilas and coworkers [ 29 ], who demonstrated a large increase in cortisol levels after the air CVT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we demonstrated that the air CVT, a useful medical examination procedure that assesses the horizontal semicircular canal function of each labyrinth and is severe enough to provoke nystagmus and dizziness, is a powerful activator of the HPA axis, a finding that aligns with previous observations made by Dagilas and coworkers [ 29 ], who demonstrated a large increase in cortisol levels after the air CVT.…”
Section: Discussionsupporting
confidence: 92%
“…Given the potential interaction between the vestibular and autonomic pathways, this finding could be explained by the reduction in the SAM system activity following vestibular stimulation [ 30 ]. Several clinical observations and animal studies have suggested a link between vestibular and autonomic systems [ 12 , 29 , 31 , 32 ]. The nature of these interactions, however, is complex and has not been fully defined.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of UVD and BVD in rats and guinea pigs have found no long-term changes in either glucocorticoid levels or their receptors (Gliddon et al, 2003;Lindsay et al, 2005;Russell et al, 2006;Zhang et al, 2005Zhang et al, , 2008. Vertigo artificially induced in control subjects by caloric irrigation of the external auditory canal has been shown to cause an increase in cortisol levels (Daglias et al, 2005); however, it is unknown whether this has any effect on cognition.…”
Section: Why Should Manipulation Of the Vestibular System Have Effectmentioning
confidence: 99%
“…Dagilas et al (2005) investigated the stress response evoked by vestibular stimulation in healthy volunteers by measuring serum cortisol levels at the point of maximal nystagmus while undergoing caloric stimulation. Cortisol levels were found to be significantly elevated above resting levels, while the serum concentrations of glutamate, glycine, and GABA were reduced (Dagilas et al, 2005).…”
Section: Stress and Vestibular Compensation In Manmentioning
confidence: 99%
“…Cortisol levels were found to be significantly elevated above resting levels, while the serum concentrations of glutamate, glycine, and GABA were reduced (Dagilas et al, 2005). In a preceding detailed study, Kohl (1985) demonstrated that cross-angular rotatory vestibular stimulation potently stimulated ACTH, noradrenaline, and adrenaline secretion, in a pattern consistent with a vestibular-evoked stress response.…”
Section: Stress and Vestibular Compensation In Manmentioning
confidence: 99%